THE PERCEIVED IMPACT OF CLIMATE CHANGE ON A SELECTED MANILA BAY-AREA HOTEL - David, Marck Bryan A. (ASEAN Journal on Hospitality and Tourism, 2015)
Climate change, an increasingly apparent phenomena, has the potential to affect the tourism industry. This exploratory paper was created to (1) look at the possible impacts of climate change, particularly sea-level rise, on a selected Manila-Bay area hotel; (2) explore possible changes in the operational systems of the selected hotel and propose changes into these systems; and (3) propose possible monitoring programs and policies aimed at mitigating the impact of climate change, particularly in the most vulnerable areas to climate change like the Philippines. The researcher employed a case-study method for this exploratory research. Data were then analyzed using the Climate Lens Model, in conjunction with the systems model. It was found out that storm surges, one of the indirect impacts of climate change caused by stronger typhoons, brought about changes in the operational system of the hotel. Yet, even if there were measures undertaken, these measures were only short-term, which in a climate change standpoint is inadequate due to the fact that climate change is very dynamic. It was recommended that the hotel establishment take into account a diverse range of technological, managerial, educational, policy and behavioral adaptations to deal with climate variability, based on the recommendation set by the Davos Declaration of the UNWTO.